Dynamics of Humoral and Cellular Responses in Renal Transplant Recipients Receiving 3 Doses of SARS-CoV-2 mRNA Vaccine. Issue 2 (2nd November 2022) - Arias-Cabrales, Carlos; Folgueiras, Montserrat; Faura, Anna; Eguia, Jorge; Padilla, Eduardo; Hurtado, Sara; Ribera, Laura; Echeverria-Esnal, Daniel; Pérez-Sáez, María José; Redondo-Pachón, Dolores; Burballa, Carla; Buxeda, Anna; et al.
Abstract : Background: The original SARS-CoV-2 vaccination regimen (2 doses) induces insufficient short-term response in kidney transplant (KT) recipients. This study assessed the response to a third dose and the long-term immunogenicity after 2 doses in KT. Methods: We analyzed the dynamics of the humoral and cellular response by monitoring SARS-CoV-2 IgG antibodies against the Spike-protein (IgG-Spike) and QuantiFERON SARS-CoV-2 IFN-γ release assay 6 mo after the second dose (T2) and 28 d after the third dose of mRNA vaccines (T3) to KT and controls (dialysis patients and healthy individuals). Results: At T2, the percentage of IgG-Spike+ KT and dialysis patients decreased (KT 65.8%–52.6%, hemodialysis 92.6–81.5%, and peritoneal dialysis 100%–90%), whereas 100% of healthy controls remained positive. About the cellular response, the percentage of responders decreased in all groups, especially in KT (22.4%–9.2%, P  = 0.081). At T3, 92% of KT, 94%–98% of dialysis patients, and 100% of healthy controls were IgG-Spike+. In terms of antibody titers, patients and controls showed a reduction between T2 and T3 and about 80% of dialysis patients and 100% of controls achieved high titers after the third dose (>1479.5 Binding Antibody Units/mL), whereas this percentage was only 50% in KT. With respect to the cellular response, only KT displayed a significant rise after the third dose. Conclusions: The third dose of mRNA vaccine improves both humoral and cellular responses, but less effectively in KT compared with dialysis patients and healthy controls. Abstract :